Media Stamp Game untuk Meningkatkan Kemampuan Berhitung Anak Slow Learner di Sekolah Dasar - Suci Wulandari; Susanti Prasetyaningrum (Psympathic : Jurnal Ilmiah Psikologi, 2018)
Slow learner children may find it hard to learn abstract and symbolic concepts, which could lead to difficulties in math learning, such as sum. The stamp game is a learning media with a concept to teach count operation (sum) with concrete form that is easy to use by children with simple steps and used repeatedly to reinforce the concepts. Thus, it may improve math ability in slow learner children. The purpose of this study is to improve the ability of counting operations (sum) in elementary school students who are slow learner by using the stamp game. This study used single case experimental design. The participants were three slow learner children selected using purposive sampling technique. The results of the research show that the stamp game can improve counting (sum) ability in elementary school students who are a slow learner.